HUBUNGAN KARAKTERISTIK PETANI TEPI HUTAN DENGAN PERILAKU MEREKA DALAM MELESTARIKAN HUTAN LINDUNG DI 12 DESA PROPINSI LAMPUNG - Pitojo Budiono; Amri Jahi; Margono Slamet; Djoko Susanto (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2006)
Farmers living in the near by forest villages fullfilled their living needs mainly through exploiting the forest resources. Controlled forest exploitation created serious forest degradation. The annual forest degradation rate was 2 to 6 million hectares. In this relation the objectives of this study were to asses the relationship of farmer’s characteristics and their competencies in forest conservation. The population of this study was four hundreds farmers living in 12 village near the national forest park. Data was collected from may to october 2005. Data obtained were analized by Kendall W Concordance procedure and SEM. The result pointed out that farmers lacked competencies in both farm and forest conservation.